2016
DOI: 10.1037/law0000066
|View full text |Cite
|
Sign up to set email alerts
|

A psychometric assessment of the Community Attitudes Toward Sex Offenders (CATSO) Scale: Implications for public policy, trial, and research.

Abstract: Public attitudes toward sex offenders have contributed to the passage of a number of sex offender-specific laws. Following these laws, researchers developed the Community Attitudes Toward Sex Offenders (CATSO) scale, yet there is debate over the most appropriate factor structure, and no studies to date examine its predictive utility. The current study tested the CATSO factor structure, and explored construct and predictive validity in a community sample. Results included identification of (a) a 2-factor model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In regard to other factors, only five known studies have considered community member level of education as an explanatory variable for sex offender stigma, with four studies (Pickett et al, 2013;Shackley, Weiner, Day, & Willis, 2013;Wevodau et al, 2016;Willis et al, 2013) finding that higher education was related to less stigma toward sex offenders, including cognitive, affective, behavioral, and knowledge components of such stigma. The other study (Mancini, Shields, Mears, & Beaver, 2010) found no relationship between more formal education and endorsing restrictions on where sex offenders can live.…”
Section: Predictors Of Stigma Toward Sex Offendersmentioning
confidence: 99%
See 4 more Smart Citations
“…In regard to other factors, only five known studies have considered community member level of education as an explanatory variable for sex offender stigma, with four studies (Pickett et al, 2013;Shackley, Weiner, Day, & Willis, 2013;Wevodau et al, 2016;Willis et al, 2013) finding that higher education was related to less stigma toward sex offenders, including cognitive, affective, behavioral, and knowledge components of such stigma. The other study (Mancini, Shields, Mears, & Beaver, 2010) found no relationship between more formal education and endorsing restrictions on where sex offenders can live.…”
Section: Predictors Of Stigma Toward Sex Offendersmentioning
confidence: 99%
“…Public sociodemographic predictors of sex offender stigma differ slightly from general criminal offender stigma on other variables. For example, most research has found no gender differences in many sex offender stigma studies (e.g., Rade et al, 2016;Sahlstrom & Jeglic, 2008;Wevodau et al, 2016), although females have reported keeping further social distance from sex offenders, feeling less positively toward sex offenders, and supporting punitive laws (Koon-Magnin, 2015;Pickett et al, 2013;Willis et al, 2013); males have been found to support some community notification policies and view them as effective (Koon-Magnin, 2015). Some studies have also found females to be more "pro-victim" in mock juror scenarios involving sex abuse cases (e.g., Quas, Bottoms, Haegerich, & Nysse-Carris, 2002).…”
Section: Predictors Of Stigma Toward Sex Offendersmentioning
confidence: 99%
See 3 more Smart Citations